Open High School (SMA) as an Alternative Education to Reduce Dropout Rates (Aps) in East Lombok Regency - Saminah, Jawahir Intan Hairul; Badarudin, Badarudin; Subhani, Armin (Journal of Educational Sciences, 2025)
The high dropout rate (APS) at the senior secondary level in East Lombok Regency reflects the limited effectiveness of the nine-year compulsory education program, driven by early marriage, economic constraints, and limited access. This study analyzes the role of the Open Senior High School (SMA Terbuka) in reducing dropout rates and explores strategies for strengthening its implementation. Using a descriptive qualitative case study at SMA Terbuka 1 Sakra Timur, data were obtained through interviews, observations, and documentation, and analyzed with Miles and Huberman’s interactive model. Findings indicate that SMA Terbuka offers an inclusive alternative through decentralized Learning Activity Centers (TKB) supported by tutor teachers, with a flexible curriculum adapted to students’ needs. Since 2021/2022, the program has reduced dropout rates and produced hundreds of graduates. Community and government support, flexible scheduling, and home-visit mentoring are critical factors. SMA Terbuka significantly expands educational access, and its optimization requires strengthened facilities, digital resources, and teacher capacity to support SDG 4 on quality education.